A Solution-Processed Tetra-Alkoxylated Zinc Phthalocyanine as Hole Transporting Material for Emerging Photovoltaic Technologies. (13th November 2018) - Zanotti, Gloria; Mattioli, Giuseppe; Paoletti, Anna Maria; Pennesi, Giovanna; Caschera, Daniela; Maman, Nitzan; Visoly-Fisher, Iris; Misra, Ravi K.; Etgar, Lioz; Katz, Eugene A.
Abstract : A tetra- n -butoxy zinc phthalocyanine ( n -BuO)4 ZnPc has been synthesized in a single step, starting from commercial precursors, and easily purified. The molecule can be solution processed to form an effective and inexpensive hole transport layer for organic and perovskite solar cells. These appealing features are suggested by the results of a series of chemical, optical, and voltammetric characterizations of the molecule, supported by the results of ab initio simulations. Preliminary measurements of ( n -BuO)4 ZnPc-methylammonium lead triiodide perovskite-based devices confirm such suggestion and indicate that the interface between the photoactive layer and the hole transporting layer is characterized by hole-extracting and electron-blocking properties, potentially competitive with those of other standards de facto in the field of organic hole transport materials, like the expensive Spiro-OMeTAD.